Field evaluation of seven SARS-COV-2 antigen assays - Yong Kwan Lim; Oh Joo Kweon; Hye Ryoun Kim; Tae-Hyoung Kim; Mi-Kyung Lee (Elsevier, 2022)
There is a global demand for rapid diagnostic tests (RDTs) for Coronavirus disease 2019 (COVID-19), and the interest in their clinical compliance is growing. In this study, we evaluated the clinical compliance of seven different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antigen RDTs. Nasopharyngeal/oropharyngeal swab specimens from COVID-19-confirmed cases and reverse-transcription PCR (RT-PCR) screening were used to evaluate the performance of seven RDTs. Using the RT-PCR and RDT results, we predicted the cycle threshold (Ct) of each target gene (E, RdRP, and N genes) which 50% (Ct50) and 95% (Ct95) detection rates were achieved in the RDTs. A total of 482 specimens were enrolled in our study: 316 specimens from COVID-19-confirmed cases and 166 RT-PCR-negative specimens. The median values of Ct50 and Ct95 for the seven RDTs were in the ranges of ranged 24.3-30.9 and 19.3-22.6 for E, 25.5-31.5 and 20.9-24.0 for RdRP, and 26.8-32.3 and 22.7-25.7 for N, respectively. The RDTs showed acceptable compliance only for specimens with high viral burdens (Ct < 20). However, the false-negative rate increased by more than 50% for most of the RDTs in low-viral burden specimens (Ct> 30). These results suggest that RDTs should not be used without molecular assays for COVID-19 screening for asymptomatic patients because of their high false-negative rates.